On the Rate of Boronate Ester Formation in ortho-Aminomethyl Functionalized Phenyl Boronic Acids‡ - Collins, Byron E. (2013)
The role of the ortho-aminomethyl functional group in phenyl boronic acids for sugar complexation is a topic of debate. To decipher its effect on the kinetics of boronate ester formation, we first performed pseudo-first order kinetics analyses at five pH values up to 4 mM in fructose, revealing a first-order kinetic dependence upon fructose. Under these conditions, the reaction is in equilibrium and does not reach completion, but at 50 mM fructose saturation is achieved revealing zero-order dependence upon fructose. This indicates rate-determining creation of an intermediate prior to reaction with fructose, which we propose involves leaving group departure of inserted solvent. Further, the region of kinetics displaying zero-order dependence has a kinetic isotope effect (KIE) of 1.42, showing involvement of a proton transfer in the leaving group departure. The ratio of forward and reverse rate constants branching from the intermediate shows that fructose is several thousand times more nucleophilic than the solvent. Overall, the data supports a mechanism where the o-aminomethyl group lowers the pK(a) of the proximal boronic acid and acts as a general-acid (as an ammonium) to facilitate leaving group departure. Consequently, by microscopic reversibility the resulting amine must perform general-base catalysis to deliver fructose.